Konsep Diri pada Remaja yang Mengalami Bullying - Galih Aditiya Wijayanto; Eni Hidayati (Jurnal Keperawatan Silampari, 2021)
This study aims to determine how the influence of bullying behavior on self-concept in adolescents. The research method used is quantitative with a causal-comparative approach. The results showed that there was an effect of bullying on self-concept in adolescents. Based on the R square test results, it is known that bullying has an impact of 51.1% to determine self-concept in adolescents, and the remaining 48.9% is influenced by something not examined in this study. In conclusion, the higher or often the teenager is bullied, the self-concept will decrease. The more often a person becomes a victim of bullying, the more negative his self-concept will be. Keywords: Bullying, Self Concept, Youth